SISTEM INFORMASI PENDAPATAN DAN PENJUALAN PADA PT. WORLD WIDE EQUIPMENT SOUTH EAST ASIA (WWESEA) - Santoso, Cahyo Budi (DIMENSI, 2016)
The purpose of this study was to determine: 1). Knowing and provide an explanation of the implementation of revenue and sales information system at PT. World Wide Equipment South East Asia (Batam). 2). To determine whether there is influence between information systems and sales revenue with the effectiveness of the company.The results showed the application of information systems and information revenue and sales revenue at PT. World Wide Equipment South East Asia (WWESEA) are adequate and have been qualified and characteristics. Information systems and sales revenue despite the Company is still in the development stage, through the management-level managers below.Results of research on the evaluation of efficiency in project cost control Spudcans Lisa is located on a promontory Singkuang showed favorable revenue and earnings that are not favorable to any such revenues. But in general there is a lucrative income of SGD 1.700.000 million reduced SGD 1.46495 million multiplied by 100% of the revenue to the project SPUDCANS LISA SGD 235.050.From these results it can be concluded that the revenue and sales information system at PT. World Wide Equipment South East Asia has been good and adequate. This looks to have fulfilled all the indicators of income and sales information systems. The effectiveness and efficiency of revenue and sales have not fully maximized, because there is a difference masti unfavorable in some jobs that have been planned, although overall has occurred efficient.